Phytoplankton dynamics in a highly eutrophic estuary in tropical Brazil - Marilene Felipe Santiago; Maria da Glória Gonçalves da Silva-Cunha; Sigrid Neumann-Leitão; Kátia Muniz Pereira da Costa; Gislayne Cristina Borges Palmeira; Fernando de Figueiredo Porto Neto; Fabiana Santana Nunes (Brazilian Journal of Oceanography, 2010)
The port of Recife in northeastern Brazil is an important ecological and social area but little is known about its environmental quality. Observations, sampling and measurements of phytoplankton were performed during spring and neap tides in the dry (January-February, 2005) and rainy (June, 2005) seasons to assess the environmental quality of the port of Recife. The area had chlorophyll-a concentrations ranging from 3.30 to 54.40 mg m-3, the highest values occurring at low tide during the dry season. A total of 129 species were identified: 53 of them in the dry season and 97 in the rainy season. Diatoms were the most diverse group and comprised 75.47% of the phytoplankton collected in the dry season and 60.82% of those collected in the rainy season. The dry season was characterized by Coscinodiscus sp. and Helicotheca tamesis; the rainy season by Oscillatoria sp. and Coscinodiscus centralis. Species diversity indices varied from 1.06 to 3.74 bits cel-1. Low indices were related to the dominance of Helicotheca tamesis, Coscinodiscus centralis, Coscinodiscus sp. and Aulacoseira granulata. Seasonal forcing, rather than the estuarine flux, determined the phytoplankton community structure. The area is exposed to seasonally varying negative impacts due to metropolitan degradation and the high level of eutrophication. Para avaliar a qualidade ambiental Porto do Recife (Nordeste do Brasil), uma área ecológica e socialmente importante mas pouco investigada, observações, medições e amostragem do fitoplâncton foram realizadas durante as marés de sizígia e quadratura no período de estiagem (janeiro-fevereiro / 2005) e chuvoso (junho/2005). A área apresentou concentração de clorofila a variando de 3,30 a 54,40 mg m-3, com maiores valores registrados durante a maré baixa no período de estiagem. Um total de 129 espécies foi identificada com 53 espécies durante o período de estiagem e 97 espécies no chuvoso. As diatomáceas formaram o grupo mais diverso, com 75,47% no período de estiagem e 60,82% no chuvoso. Coscinodiscus sp. e Helicotheca tamesis caracterizaram o período de estiagem e Oscillatoria sp. e Coscinodiscus centralis o período chuvoso. A diversidade de espécie variou de 1,06 a 3,74 bits cel-1 . Os baixos índices foram relacionados com a dominância de Helicotheca tamesis, Coscinodiscus centralis, Coscinodiscus sp. e Aulacoseira granulata. A sazonalidade determinou a estrutura da comunidade fitoplanctônica, em vez do fluxo estuarino. A área é exposta sazonalmente a vários impactos negativos, devido à degradação metropolitana e ao elevado nível de eutrofização.